أثر الأوضاع الاجتماعية في فهم السنة النبوية واستنباط الأحكام الشرعية - Fajar Rachmadhani (Profetika: Jurnal Studi Islam, 2020)
The purpose this study is to discuss and uncover the urgency of understanding the hadith based on sociological conditions and the conclusion of Islamic law from it and show some examples related to it. The researcher hopes that this study will bring great benefits and great importance whether theoretical or applied contribute to it in a practical intellectual contribution to religious progress and the modern jurisprudence. This research is a qualitative inductive research, its main sources are the six Hadith books, and secondary sources are books of the principles of jurisprudence and the purposes of Sharia and information contained in magazines and websites and others. This research uses the analytical approach, so that it is used to highlight the characteristics of messages that are implemented objectively and systematically.